Incidence and outcomes of pulmonary hypertension in the Ireland. Issue 1 (29th June 2022) - Cullivan, Sarah; Lennon, Denise; Meghani, Salima; Minnock, Caitriona; McCullagh, Brian; Gaine, Sean
Abstract : Introduction: Pulmonary hypertension (PH) is a progressive disease of the pulmonary vasculature, which is characterised by premature morbidity and mortality. The aim of this study is to define the characteristics of PH in the national PH unit (NPHU) in Ireland between 2010 and 2020. Methods: Cases of PH which were referred to the NPHU between 2010 and 2020 were included. PH was defined as a mean pulmonary artery pressure ≥25 mm Hg at right heart catheterisation. Results: Four hundred and fifteen cases of PH were identified during the study period. Group 1 pulmonary arterial hypertension (PAH) accounted for 39% (n=163) of cases, with a calculated annual incidence of 3.11 per million population (95% CI 1.53 to 4.70). The leading PAH subgroup was connective tissue disease-associated PAH (CTD-PAH), which was responsible for 49% of PAH referrals. This was followed by idiopathic PAH, with an estimated annual incidence of 0.63 cases per million population. The mean age at PAH diagnosis was 56±15 years and 86% (n=111) received double-combination or triple-combination therapy within the first 12 months of diagnosis. The 1-year, 3-year and 5-year transplant-free survival for PAH was 89%, 75% and 65%. This was significantly lower for individuals with CTD-PAH relative to other PAH subgroups (p<0.05). Discussion: This study describes the incidence and outcomes of PH in Ireland. While the outcomes are comparable to other centres, the incidence of PAH and specific subgroups appears low, suggesting that improved disease awareness and case recognition are required. Furthermore, the survival of individuals with CTD-PAH is poor and requires additional exploration.